(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2017)
The paper presents analysis of the storage systems used by social network sites. Namely, the social networks are one of the main driving forces behind the NoSQL database development. Facebook and Twitter were, together with other the Big Data players like Google and Amazon, first faced with the limitations of relational databases in solving their needs related to unprecedented transaction volumes, expectations of low-latency access to massive datasets, and nearly perfect service availability while operating in an unreliable environment. The first NoSQL databases arose as internal solutions created out of necessity, and not with the intention to abandon relational databases. But the main question is if, after more than ten years of development, NoSQL databases proved that they could be valuable storage solutions for social networks’ data. The paper shows that there is still a lot of room for improvement in the use of NoSQL in social networks and provides some suggestions on how NoSQL databases can bring additional value to social network sites. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.